Representasi Komunikasi Keluarga pada Film “Home Sweet Loan” Analisis Semiotika Roland Barthes - Nasution, Alya Azra Mutia; Faridah (Jurnal Dakwah dan Komunikasi, 2025)
: The movie “Home Sweet Loan” tells the story of financial problems faced by a family causing quarrels and disagreements among family members. This research emphasizes the role of film as a medium that reflects the dynamics of family life in the modern world. The research method used is qualitative with Roland Barthes semiotic analysis approach by collecting information through observation and documentation to find out the meaning of denotation, connotation and myth in family communication. The research found signs of family communication carried out by Kaluna, Father, Mother, Kamala, and Kanendra. The results show that this film represents complex family communication, where tensions and conflicts arise due to debt problems, lack of openness between family members, and the gap in parental treatment of boys and girls, commonly known as differential behavior. The movie shows how important emotional support and open communication are to dealing with adversity. The moments of reflection in the film make us as viewers realize that we can improve and understand better in the future. It is hoped that this research provides a better understanding of family communication and its relevance in a social context.